NxO emissions in response to the irrigation lower limits under different irrigation modes in a lettuce field - Hou, Maomao; Xiao, Ying; Zhu, Qinyuan; Chen, Jingnan; Huang, Huan; Jin, Qiu; Zhu, Lin; Zhong, Fenglin (International Journal of Agricultural and Biological Engineering, 2023)
Irrigation has a significant impact on NxO (N2O and NO) emissions from cultivated land, yet the N2O or NO emission among the irrigation lower limits under different irrigation modes has not been well compared. In an irrigated lettuce field, three DR (drip irrigation) lower limits were designed, including 75% (DR1), 65% (DR2) and 55% (DR3) field capacity, and one FI (furrow irrigation) lower limit (65% field capacity). The N2O and NO emission fluxes and soil nitrogen (N) forms were determined, and the linear correlation between these indicators was analyzed. Results showed that under the same irrigation regime, the N2O and NO emissions from furrow irrigation treatment increased by 36.8% and 45.2% respectively compared to that from drip irrigation treatment. The cumulative N2O and NO emissions under DR3 were 30.2% and 28.6% higher than under DR1, respectively. Moreover, DR1 was also the lowest among the four treatments in soil NO3–N concentration. The N2O and NO emission fluxes were more correlated to soil NH4+-N (r=0.88 and 0.76) or NO2–N (r=0.90 and 0.80) concentration than soil NO3–N and soluble organic N, indicating that N2O and NO were mainly produced by the soil nitrification process. When the irrigation regime was the same, N2O and NO emissions were lower with drip irrigation than with furrow irrigation. Besides, drip irrigation with small quota but high frequency reduced N2O and NO emission compared to that with large quota but low frequency. Keywords: nitrous oxide, nitric oxide, drip irrigation, furrow irrigation, soil nitrogen DOI: 10.25165/j.ijabe.20231604.7961 Citation: Hou M M, Xiao Y, Zhu Q Y, Chen J N, Huang H, Jin Q, et al. NxO emissions in response to the irrigation lower limits under different irrigation modes in a lettuce field. Int J Agric & Biol Eng, 2023; 16(4): 159–167.